Confirmation : How a Sacrament of God's Grace Became All about Us - Gabrielli, Timothy R., 1982- (Book collections on Project MUSE., 2013)
What are we doing when we confirm teenagers? Why is the religious education of teenagers so perplexing? Why is confirmation often a moment of graduation out of parish life? Confirmation: How a Sacrament of God's Grace Became All about Us tells the story of how confirmation, more than any other sacrament, has interacted with secular culture to give rise to these kinds of pastoral challenges. At the same time, confirmation has, over the course of the twentieth century, become a sacramental stamp of approval for various Catholic renewal movements. The cultural shifts of the last century have led to various theological themes for confirmation, creating a crisis of meaning today. Is confirmation a personal choice for faith, or is it the deepening of an ongoing relationship with the Divine? Timothy R. Gabrielli gives us a fresh approach for addressing these pressing questions. -- Publisher.